Impact of COVID-19 pandemic in children using non-invasive ventilation: a thematic analysis of caregivers answers to a survey study - Dobson, Lauren; Milne, Ella; Halperin, Heather; Olmstead, Deborah; Scott, Shannon D.; Castro-Codesal, Maria L. (Frontiers in Sleep, 2024)
The COVID-19 pandemic has resulted in drastic changes in people's lives, more so in individuals with chronic conditions, such as children with chronic respiratory disorders requiring home non-invasive ventilation.Our research question was: 'How has the COVID-19 pandemic affected the daily lives of children using home NIV and their families and their NIV adherence?Methods: An anonymous online survey was administered to caregivers of pediatric patients using home NIV followed at the Stollery Pediatric NIV Program in Alberta, Canada, between September 2020 and September 2021. Thematic analysis was conducted for the identification of emerging themes.Results/Findings: Four themes were identified: 1) positive effects, 2) negative effects, 3) neutral effects, and 4) adherence to NIV. effects of COVID-19 on children and families were reported by 55 respondents (57% response rate). Positive effects included a slower lifestyle, more family time, and less recurrent acute respiratory illness.Negative effects included increased parental anxiety, prolonged social isolation beyond imposed restrictions, and limited access to health supplies. Despite these negative effects, 90% of respondents reported adequate maintenance or even increases in their child's NIV use. A general sense of benefit in the virtual specialized care model was also highlighted.COVID-19 resulted in varying levels of impact on the lives of children using NIV, not unlike the general population. Negative effects, however, appeared to intensify in these technology-dependent children. NIV adherence, however, was prioritized by families and even increased during COVID-19. Further research is needed to analyse the potential benefits of virtual models of specialized care.